Hubungan Persepsi Guru Dalam Pembelajaran Tatap Muka Dengan Kemandirian Pada Anak Usia 5-6 Tahun - Nurhenti Dorlina Simatupang; Indarwati Sholikhah (Early Childhood Islamic Education, 2023)
The purpose of the study was to determine the relationship between teacher perceptions of face-to-face learning and independence in children aged 5-6 years. This type of research is quantitative correlational. the independent variable (independent), namely the teacher's perception and the dependent variable (dependent), namely the independence of the child. The research population is all kindergarten teachers in Waru sub-district, Sidoarjo district totaling 464. The sampling technique is purposive sampling, where the sample selection is carried out according to predetermined criteria, namely schools with minimum accreditation B and teachers who teach in Kindergarten class B. The survey method in the form of a google form or a questionnaire is the data collection technique used. Data analysis techniques consist of: validity test with Product Moment formula, reliability test with Cronbach Alpha formula and correlation test with Person Correlation formula. The calculation using the person correlation formula aims to determine whether or not there is a significant relationship between the teacher's perception and the child's independence. Based on the calculation of the correlation test, it was obtained that r arithmetic was 0.471 and r table with a significant level of 5% = 0.198, in other words r arithmetic > r table (0.471> 0.198) so it could be concluded that there was a strong enough relationship between teacher perceptions and children's independence.